New perspectives on mTOR inhibitors (rapamycin, rapalogs and TORKinibs) in transplantation. (6th March 2016) - Waldner, Matthias; Fantus, Daniel; Solari, Mario; Thomson, Angus W.
Abstract : The macrolide rapamycin and its analogues (rapalogs) constitute the first generation of mammalian target of rapamycin (mTOR) inhibitors. Since the introduction of rapamycin as an immunosuppressant, there has been extensive progress in understanding its complex mechanisms of action. New insights into the function of mTOR in different immune cell types, vascular endothelial cells and neoplastic cells have opened new opportunities and challenges regarding mTOR as a pharmacological target. Currently, the two known mTOR complexes, mTOR complex (mTORC) 1 and mTORC2, are the subject of intense investigation, and the introduction of second‐generation dual mTORC kinase inhibitors (TORKinibs) and gene knockout mice is helping to uncover the distinct roles of these complexes in different cell types. While the pharmacological profiling of rapalogs is advanced, much less is known about the properties of TORKinibs. A potential benefit of mTOR inhibition in transplantation is improved protection against transplant‐associated viral infections compared with standard calcineurin inhibitor‐based immunosuppression. Preclinical and clinical data also underscore the potentially favourable antitumour effects of mTOR inhibitors in regard to transplant‐associated malignancies and as a novel treatment option for various other cancers. Many aspects of the mechanisms of action of mTOR inhibitors and their clinical implications remain unknown. In this brief review we discuss new findings and perspectives of mTOR inhibitors in transplantation.